(untitled) (Journal of the Bangladesh Agricultural University, 2019)
The experiment was carried out at the Horticulture Farm of Bangladesh Agricultural University, Mymensingh to investigate the influence of organic and inorganic fertilizers with irrigation intervals on the growth and yield of carrot during November, 2016 to March, 2017. Different days interval irrigation were applied namely no irrigation (I0), 7 days interval (I7), 15 days interval (I15) and 30 days interval (I30). Organic and inorganic fertilizers were given as treatments like control (no fertilizer) (F0), vermicompost (F1), mixed fertilizer (2/3 vermicompost + 1/3 inorganic fertilizer) (F2), inorganic fertilizer (F3). The experiment was laid out in RCBD (randomized complete block design) with three replications. Irrigation interval treatments showed significant influence on growth and yield related parameters of carrot. Plant height, other growth related parameters and yield were found significantly different considering the effect of irrigation and fertilizers treatments. Considering the effect of irrigation, the highest and the lowest plant height was obtained 45.35 cm and 39.77 cm from 7 days interval irrigation and control, respectively. The highest marketable yield (42.47 t/ha) was found from 7 days irrigation interval and it was 27.40% higher compared to control (30.83 t/ha). Mixed of organic and inorganic fertilizer (F2) gave the highest plant height (47.58 cm) and the lowest plant height (35.08 cm) was found from the control treatment. Gross yield and marketable yield per hectare were higher 21.21% and 22.03% in F2 compared to control treatment. Considering the treatment combination, irrigation at 7 days interval with mixed fertilizer (I7F2) produced the highest plant height (50.42 cm), number of leaves (11.67), diameter of root (3.90 cm), length of root (23.20 cm), fresh weight of individual root (106.20 g), gross yield (53.66 t/ha) and marketable yield (46.91 t/ha). The lowest plant height (32.75 cm), number of leaves (7.83), diameter of root (3.10 cm), length of root (13.00 cm), fresh weight of individual root (65.00 g), gross yield (32.00 t/ha) and marketable yield (26.72 t/ha) were found from the treatment combination of no irrigation with no fertilizer (I0F0). Gross yield and marketable yield per hectare were 40.37% and 43.04% higher, respectively in irrigation at 7 days interval with mixed fertilizer than other treatments combination. Irrigation interval at 7 days with mixed fertilizer had the most positive effect for the production of carrot. J Bangladesh Agril Univ 17(3): 338–343, 2019